Does e-cigarette experimentation increase the transition to daily smoking among young ever-smokers in France?. (1st March 2020) - Chyderiotis, Sandra; Benmarhnia, Tarik; Beck, François; Spilka, Stanislas; Legleye, Stéphane
Highlights: Daily smoking is still highly popular among French adolescents aged 17. E-cigarettes are largely experimented with among French adolescents aged 17. Among ever-smokers, those who had ever used e-cigarettes were less likely to become daily smokers at 17. Same conclusions were reached whether e-cigarettes were tried before or after smoking. Abstract: Introduction: According to multiple studies, e-cigarette use among adolescents is associated with subsequent smoking initiation. However, little is known about its effect on the transition from smoking initiation to daily smoking. Methods: Using retrospective data from a French national representative survey collected in 2017 (n = 39, 115), we analyzed the role of ever using e-cigarettes on daily cigarette smoking status at 17 among ever smokers (n = 21, 401). Risk-ratios (RR) were computed through modified Poisson regressions with an inverse probability of treatment weighting (IPTW) approach. Results: Among French adolescents aged 17, 16.8 % declared current e-cigarette use (1.9 % reported daily use) and 34.1 % cigarette smoking (25.1 % reported daily smoking). Among ever-smokers, adolescents who declared having ever used e-cigarettes were less likely than those who did not to transition to daily smoking at 17: RR = 0.62 95 %CI [0.60 – 0.64]. We found similar results for those who experimented with e-cigarettes before initiating smoking, RR = 0.76 95 %CI [0.66 – 0.89]. Conclusions: Our results found no evidence of an increased risk of transitioning to daily smoking at 17 among ever-smokers who also experimented with e-cigarettes. Further studies should investigate the longer-term role of vaping on future smoking habits with the use of causal inference methods.